Vainglory: the forgotten vice - DeYoung, Rebecca Konyndyk 1971- (William B. Eerdmans Publishing Company, 2014)
Vainglory-- a keen desire for attention and approval. Although contemporary culture has largely forgotten about vainglory, it was on the original list of seven capital vices and is perhaps more dangerous than ever today. DeYoung tells the story of this vice, moving from its ancient origins to its modern expressions. She defines vainglory, gives examples from popular culture, and discusses other vices associated with it such as hypocrisy and boasting. She then explores personal spiritual practices that can help us resist it and community practices that can help us handle glory well